2021
DOI: 10.3389/frobt.2021.627958
|View full text |Cite
|
Sign up to set email alerts
|

Do Privacy Concerns About Social Robots Affect Use Intentions? Evidence From an Experimental Vignette Study

Abstract: While the privacy implications of social robots have been increasingly discussed and privacy-sensitive robotics is becoming a research field within human–robot interaction, little empirical research has investigated privacy concerns about robots and the effect they have on behavioral intentions. To address this gap, we present the results of an experimental vignette study that includes antecedents from the privacy, robotics, technology adoption, and trust literature. Using linear regression analysis, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 79 publications
0
10
1
Order By: Relevance
“…As the high-frequency words identified in the third part were not related to the concept of social influence, it contradicts the findings of Gursoy et al (2019) , Lu et al (2019) , Lutz and Tamò-Larrieux (2021) . One of the possible reasons is that most users do not know that hotels provide robot services before they check into hotels, the human–robot experience is out of expectation, so the social influence does not work.…”
Section: Resultscontrasting
confidence: 78%
“…As the high-frequency words identified in the third part were not related to the concept of social influence, it contradicts the findings of Gursoy et al (2019) , Lu et al (2019) , Lutz and Tamò-Larrieux (2021) . One of the possible reasons is that most users do not know that hotels provide robot services before they check into hotels, the human–robot experience is out of expectation, so the social influence does not work.…”
Section: Resultscontrasting
confidence: 78%
“…Since SNS users are usually required to provide private information on their personal profile, they normally express concerns about their privacy (Lin and Liu, 2012 ; Lutz and Tamò-Larrieux, 2021 ). The privacy risk of SNSs has been viewed as a significant factor that affects users' social interactions and usage behaviors (Hajli and Lin, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We address the fact that individual concerns for information privacy influence users' behaviors on SNSs. It is important to understand privacy concerns beyond binary decisions to withhold or disclose information (Osatuyi, 2015 ; Lutz and Tamò-Larrieux, 2021 ). Moreover, the theory argument in the privacy paradox and inconsistent empirical results provide us with a research objective to reconcile the inconclusive arguments.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the CASA perspective, the psychology of close relationships might offer an important means of predicting privacy concerns. Lutz and Tamò-Larrieux's (2021) research on social robots found that social influence is a key factor in privacy concerns: the degree the user anthropomorphizes social robots is directly related to the degree of privacy concerns they bear. Thus, it can be inferred that users' privacy concerns may be affected by the extent to which they evaluate an AI agent to be worthy of a social relationship.…”
Section: Psychology Of Close Relationships: Intimacy Para-social Inte...mentioning
confidence: 99%
“…In accordance with increasing awareness of privacy-related issues, recent studies have identified user privacy as the most prominent concern (Aleipis & Patsakis, 2017;Liao et al, 2019), although theorization is still in its infancy. While a more rigorous approach is applied in some studies to elucidate the formation and effects of user privacy (Lutz & Newlands, 2021;Lutz & Tamò-Larrieux, 2021), investigating the social nature of human-agent communication can offer a significant contribution to the related field.…”
Section: Introductionmentioning
confidence: 99%